Discourse of Women's Body Construction in Advertising and Promotion "Lovely Nia" and "Alitaren" - Hajidah Fildzahun Nadhilah Kusnadi (Jurnal Spektrum Komunikasi, 2022)
The emergence of women who are often the subject of visualization of mass media advertisements is largely due to the perception of the low status of women in the institutions adopted by our society. Ads that standardize women's ideal bodies prove how men (especially in ad production) can create women to fit their "sexy or beautiful" fantasies. Advertising as a mass communication system, now tends to become a parameter and implementation that creates gender biases and preserving the construction of the female body. So that it’s considered not excessive regarding David Crystal's statement that advertising is the most colossal cultural product, when viewed from the perspective of ideology, morals and aesthetics. Using Norman Fairclough's critical discourse analysis, this study explores how 'Lovely Nia' discusses the construction of the female body in advertisements and social media promotions 'Lovely Nia' and 'Alitaren' how the concept of patriarchal ideology plays a role in this construction. The findings of this study are to make the concept of beauty an important asset that must be owned and cultivated by women and the discourse on the construction of the female body makes women still positioned as objects, especially when women have become wives. 'Lovely Nia' and 'Alitaren' still apply the malegaze concept in their advertisements and promotions both offline and online. Even though women place themselves as subjects who have full power over their body shape. The absence of men from advertising and social media promotions does not promise the release of women from patriarchal culture.